Effect of inspiratory muscle training on swim time and pulmonary function in high performance young swimmers (Revista Chilena de Rehabilitación y Actividad Física, 2021)
The respiratory system can limit physical performance at high intensities of effort, even in trained subjects, so it is proposed that inspiratory muscle training (IMT) could improve swim time and lung function in young high-performance swimmers. The purpose was to determine the effect of EMI on maximal inspiratory pressure (MIP), maximal voluntary ventilation (MVV) and its influence on swim time. Six swimmers (mean age 15.7 ± 1.0 years) underwent a series of physiological and physical performance tests before and after IMT, including (1) lung function measurements, MIP, MVV15, (2) 200 m timed swim tests. All continued with their usual training of 18 hours per week. The IMT used a portable valve, pressure threshold independent flow at 70 % of MIP, performed 30 repetitions twice a day for three weeks, for a total of 1080 repetitions. After IMT, MIP increased significantly (p = 0.028) with 13.8 % change, MVV15 decreased significantly (p = 0.028) with -23 % change, total swim times showed no significant difference (p = 0.6) with 0.6 % change and a positive trend in the 150-200 m stretch (-0.1 %). Thus, three weeks of IMT in high performance swimmers has a positive effect on MIP and MVV15, induced physiological improvements that can be incorporated into training. However, it did not improve swim time in the 200 m event.
Keywords: Respiratory muscles; performance; inspiratory muscle training; swimming; lung function